Some new classes for triad design - Ibrahim, Haslinda; Saa, Tareq Abu; Kalmoun, El Mostafa (Pushpa Publishing House, 2011)
Triad design is a class of designs introduced by Ibrahim and Wallis in [5], for arranging the distinct triples that satisfy several properties. The purpose of this paper is to present algorithms for constructing new triad designs for v = 7, 11, 13, 17, 19 and 23. We make use of the idea of difference set method to generate a starter using addition modular v.